The Political Economy of Local Cinema: A Critical Introduction - Rajala, Anne; Lindblom, Daniel; Stocchetti, Matteo (Peter Lang International Academic Publishing Group, 2020)
The globalization and digitalization of cultural markets presents formidable challenges for local cinema and storytelling. The essays in this collection address some of these challenges from the perspective of a critical political economy of local cinema. Inspiring these contributions is the effort of supporting local cinema as a form of valuable storytelling that is at risk of market-driven extinction because of the greater commercial viability of global or Hollywood cinema and national cinema.